2017
DOI: 10.1186/s12879-017-2236-9
|View full text |Cite
|
Sign up to set email alerts
|

Why being an expert – despite xpert –remains crucial for children in high TB burden settings

Abstract: BackgroundAs access to Xpert expands in high TB-burden settings, its performance against clinically diagnosed TB as a reference standard provides important insight as the majority of childhood TB is bacteriologically unconfirmed. We aim to describe the characteristics and outcomes of children with presumptive TB and TB disease, and assess performance of Xpert under programmatic conditions against a clinical diagnosis of TB as a reference standard.MethodsRetrospective review of children evaluated for presumptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…All children were tested for mycobacteria in sputum, gastric or nasogastric lavage fluid but we did not obtain positive culture results. This is largely in accordance with previous studies [17] and confirmed the paucibacillary nature of childhood TB. In addition mycobacterial culture analyses were hampered by insufficient sample volumes gained from the majority of young children included in this study ( …”
Section: Study Population and Methodssupporting
confidence: 93%
“…All children were tested for mycobacteria in sputum, gastric or nasogastric lavage fluid but we did not obtain positive culture results. This is largely in accordance with previous studies [17] and confirmed the paucibacillary nature of childhood TB. In addition mycobacterial culture analyses were hampered by insufficient sample volumes gained from the majority of young children included in this study ( …”
Section: Study Population and Methodssupporting
confidence: 93%
“…Low utilisation of Xpert® has been illustrated in other low income, high TB burden countries both in adults and children [ 47 49 ]. From surveys of implementation in high TB burden countries including Kenya, reasons associated with low utilisation included operational issues like power outages and poor specimen referral; doubts about impact to TB morbidity and mortality; preference to trust clinical acumen; low sensitivity especially in children; challenges in getting good specimens and false negatives; and lack of awareness amongst health care workers and patients [ 45 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the era of the GeneXpert and Xpert Ultra [ 9 , 10 ], challenges remain for TB diagnosis in children, which highlights the fact that better diagnostics for children might have to be based on host immune responses rather than pathogen detection. However, none of the currently available immune-diagnostic tests, including the tuberculin skin test (TST) and interferon (IFN)-γ release assays (IGRA), can distinguish between latent Mycobacterium tuberculosis (M.tb) infection (LTBI) and TB disease, or more importantly distinguish between TB disease and other respiratory infections 11 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%